Bridging the continuum: Analysis of the alignment of undergraduate and postgraduate accreditation standards. (1st September 2014) - Andrew, Susan E.; Oswald, Anna; Stobart, Kent
Abstract: Several influential national/international bodies including The Bologna Accord, The Carnegie Foundation and The Future of Medical Education in Canada (FMEC) have called for increased coordination across the medical education continuum. FMEC recognizes accreditation as a "powerful lever" and encourages the alignment of undergraduate and postgraduate standards. The Carnegie Foundation includes a similar call for the creation of a more coherent accreditation system. As a first step, using the Canadian context, we present a methodological approach that assesses the example of how well LCME/CACMS undergraduate accreditation standards align with the Royal College of Physician and Surgeons of Canada (RCPSC) postgraduate training standards. We analyzed how closely the 132 LCME/CACMS Medical School accreditation standards aligned with the 155 post-graduate standards from the RCPSC accreditation General Standards (A and B). This comparative evaluation demonstrates that the standards do not align closely. Gaps, redundancies and key differences are highlighted. These results are the first step in understanding how accreditation needs to be adapted and re-aligned across the education continuum to provide consistent and coordinated training and these methods could easily be applied to other contexts and jurisdictions.